2022
DOI: 10.1088/1748-605x/ac812f
|View full text |Cite|
|
Sign up to set email alerts
|

Calcium and phosphorus co-doped carbon dots enhance osteogenic differentiation for calvarial defect repair in situ

Abstract: Calvarial bone defect remains a clinical challenge due to the lack of efficient osteo-inductive agent. Herein, a novel calcium and phosphorus codoped carbon dot (Ca/P-CD) for bone regeneration was synthesized using phosphoethanolamine and calcium gluconate as precursors. The resultant Ca/P-CDs exhibited ultra-small size, stable excitation dependent emission spectra and favorable dispersibility in water. Moreover, Ca/P-CDs with good biocompatibility rapidly entered the cytoplasm through endocytosis and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The XPS results (Figure S5 and Table S2) confirmed that TPP copoly -CDs contain mainly four elements, C, O, N, and P, and each element atomic ratio in TPP copoly -CDs was C (74.89%), O (18.76%), N (4.46%), and P (1.9%). Importantly, the two peaks at 133.1 and 132.6 eV in the P 2p spectrum (Figure S5c) were derived from P–C and P–(C 6 H 5 ) 3 , respectively. , As is schematically shown in Figure S5d, the high-resolution C 1s spectrum of TPP copoly -CDs was fitted to three distinctive peaks at 284.7, 285.0, and 288.3 eV, corresponding to C–C/CC, C–O/C–N, and CO, respectively. The O 1s XPS spectrum (Figure S5e) presented three O states of C–OH at 533.2 eV, CO at 532.3 eV, and C–O–C at 531.6 eV. In the N 1s spectrum (Figure S 5f), the characteristic peaks at binding energies of 400.1 and 399.3 eV were classified as N–C and N–H, respectively . Additionally, the elemental analysis results of TPP copoly -CDs are shown in Table S3.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The XPS results (Figure S5 and Table S2) confirmed that TPP copoly -CDs contain mainly four elements, C, O, N, and P, and each element atomic ratio in TPP copoly -CDs was C (74.89%), O (18.76%), N (4.46%), and P (1.9%). Importantly, the two peaks at 133.1 and 132.6 eV in the P 2p spectrum (Figure S5c) were derived from P–C and P–(C 6 H 5 ) 3 , respectively. , As is schematically shown in Figure S5d, the high-resolution C 1s spectrum of TPP copoly -CDs was fitted to three distinctive peaks at 284.7, 285.0, and 288.3 eV, corresponding to C–C/CC, C–O/C–N, and CO, respectively. The O 1s XPS spectrum (Figure S5e) presented three O states of C–OH at 533.2 eV, CO at 532.3 eV, and C–O–C at 531.6 eV. In the N 1s spectrum (Figure S 5f), the characteristic peaks at binding energies of 400.1 and 399.3 eV were classified as N–C and N–H, respectively . Additionally, the elemental analysis results of TPP copoly -CDs are shown in Table S3.…”
Section: Resultsmentioning
confidence: 95%
“…19, 44 As is schematically shown in Figure S5d, the high-resolution C 1s spectrum of TPP copoly -CDs was fitted to three distinctive peaks at 284.7, 285.0, and 288. 51 Additionally, the elemental analysis results of TPP copoly -CDs are shown in Table S3. The content of C on TPP copoly -CDs is relatively higher (56.03%) compared with TPP free -CDs (49.67%).…”
Section: Target-oriented Synthesis Of Tpp Copoly -Cds Bymentioning
confidence: 99%
“… Ca/P-CDs ethanolamine phosphate, alcium gluconate Ca/P-CDs have stable excitation-dependent emission spectra and well dispersion in water, upregulated the expression of bone differentiation-related genes, including ALP, RUNX2 and OCN. 396/480 [ 92 ] Mg-CDs Lycium ruthenicum, MgCl 2 The appropriate concentration of Mg-CDs is suitable for long-term cell growth, and the cells have better growth, proliferation and osteogenic differentiation ability, showing great potential in bone tissue regeneration. 465/537 [ 93 ] PCL/PVA-TCP-CD ammonium hydrogen citrate, Gallus egg-shells The addition of only 1 w t% of CDs and TCP3 to PCL/PVA increased ALP activity and cell proliferation rates, while the synergistic effect of CDs/TCP3 resulted in the highest rates of osteogenic differentiation and proliferation compared to other scaffolds.…”
Section: Biomedical Applications Of Transition Group Metal-doped Cdsmentioning
confidence: 99%
“…The resultant Ca/P-CDs facilitated the repair of bone defects and provided a new option for osteogenic nanomaterials. 70…”
Section: Categoriesmentioning
confidence: 99%
“…The results showed that the Ca/P-CDs loaded F127 hydrogel effectively promoted the repair of bone defects in vivo compared with the unloaded F127 hydrogel. 70…”
Section: Applicationsmentioning
confidence: 99%